The importance of a Biosphere Reserve of Atlantic Forest for the conservation of stream fauna - Yoshida,CE. (2014)
Preservation of terrestrial fauna and flora has been the main reason for the settlement of most protected areas in the past 30 years, but although those areas may include water bodies, this does not necessarily mean that the biodiversity of freshwater environments are also protected. In the present study, the fauna inventory of eight streams (1st, 2nd, 4th and 5th orders) of three microbasins of Japi Mountain, a Biosphere Reserve of Atlantic Forest recognised by UNESCO since 1994, located in São Paulo state, southeast of Brazil, was conducted. The hypothesis of this study is that the conservation of this area is important for the maintenance of the aquatic biodiversity of this biome, and so, this world hotspot deserves priority conservation actions. From 2005 to 2007, benthic macroinvertebrates, fishes and, eventually, anuran amphibians were sampled in these streams. The results showed that Japi Mountain contributes to the conservation of 138 taxonomic units of the aquatic biota and covers a rich and representative biodiversity of freshwater fauna of the world (0.2%), Neotropical region (0.9%), Brazil (2.4%) and São Paulo state (17.9%). The studied streams in the Environmental Protection Area help protect endangered taxa like the fishes Neoplecostomus paranensis and Pareiorhina cf rudolphi, and shelter freshwater invertebrates and fishes whose distribution is restricted to the Brazilian territory. Japi Mountain is also an important haven of species that was missing there like the frog species Vitreorana eurygnatha. Thus, this species inventory emphasises the importance of conservation actions of the freshwater environments of this Biosphere Reserve of Atlantic Forest.